العولمة الثقافية وتجلياتها من خلال الكتب العربية والغربية - لامية طالة (My University, 2018)
ملخص: يُقصد بالعولمة الثقافية تبادل الأفكار والمعلومات والمعاني والقيم بين جميع دول العالم المتقدم والنامي، بهدف تعميق العلاجات الاجتماعية وتوسيعها وتكسير الحواجز المعرفية. ويظهر ذلك من خلال تشجيع المجتمعات الاستهلاكية وتوسيع انتشار ثقافات الدول العظمى إلى الدول الأخرى، وذلك عبر التطور الكبير في الإنترنت ووسائل التواصل الاجتماعي وتسهيل وسائل النقل الجوي والسفر لجميع الدول، وتهدف العولمة إلى دمج أفكار وثقافات مجتمعات غير متكافئة وبث مؤثراتٍ غربيةٍ جديدة تتماشى مع مخططات العولمة والتي تستهدف بالدرجة الأولى الفكر الثقافي المتمثل بالعادات والتقاليد والهوية الثقافية للأفراد، حيث تلعب لعبت دورا رئيسيا في الترويج لهذه الثقافة المعولمة. Abstract: Cultural globalization means the exchange of ideas, information, meanings and values among all countries of the developed and developing world with the aim of deepening and expanding social remedies and breaking down knowledge barriers. This is reflected in the promotion of consumer societies and the expansion of the spread of the cultures of the superpowers to other countries through the great development of the Internet, the means of social communication, the facilitation of air transport and the travel of all countries. The aim of globalization is to integrate the ideas and cultures of unequal societies and to broadcast new Western influences, Which is primarily aimed at the cultural thought of customs, traditions and cultural identity of individuals, where it has played a major role in promoting this globalized culture
Keywords: كلمات مفتاحية: العولمة؛ الثقافة؛ الكتب؛ العولمة الثقافية؛ الصناعة الثقافية. ; Keywords : Globalization; Culture; Books; Cultural Globalization; Cultural Industry.